The evolutionary dynamics of endogenous retroviruses. - Katzourakis, A; Rambaut, A; Pybus, O (2005)
Endogenous retroviruses (ERVs) are vertically transmitted intragenomic elements derived from integrated retroviruses. ERVs can proliferate within the genome of their host until they either acquire inactivating mutations or are lost by recombinational deletion. We present a model that unifies current knowledge of ERV biology into a single evolutionary framework. The model predicts the possible long-term outcomes of retroviral germline infection and can account for the variable patterns of observed ERV genetic diversity. We hope the model will provide a useful framework for understanding ERV evolution, enabling the testing of evolutionary hypotheses and the estimation of parameters governing ERV proliferation.